2020
DOI: 10.1177/1468087420916380
|View full text |Cite
|
Sign up to set email alerts
|

Reactive computational fluid dynamics modelling of methane–hydrogen admixtures in internal combustion engines: Part I – RANS

Abstract: The effects of hydrogen addition to internal combustion engines operated by natural gas/methane has been widely demonstrated experimentally in the literature. Already small hydrogen contents in the fuel show promising benefits with respect to increased engine efficiency, lower CO2 emissions, extended lean operating limits and a higher exhaust gas recirculation tolerance while maintaining the knock resistance of methane. In this article, the influence of hydrogen addition to methane on a spark ignited single cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The Power-to-Gas technology 1 is a feasible solution to store excess of energy by producing hydrogen, which can then be used to power Internal Combustion Engines (ICEs), either pure or blended with conventional fuels. 2 Hydrogen can thus be considered as one of the possible solutions to achieve a climate-neutral mobility along with electric propulsion. 3 Hydrogen shows suitable chemical and physical properties to be exploited in ICEs.…”
Section: Introductionmentioning
confidence: 99%
“…The Power-to-Gas technology 1 is a feasible solution to store excess of energy by producing hydrogen, which can then be used to power Internal Combustion Engines (ICEs), either pure or blended with conventional fuels. 2 Hydrogen can thus be considered as one of the possible solutions to achieve a climate-neutral mobility along with electric propulsion. 3 Hydrogen shows suitable chemical and physical properties to be exploited in ICEs.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulent flames in spark-ignition engines resemble highly wrinkled laminar flames; 3 hence, the combustion process is governed by the (fast) chemical reaction rates, whereas the turbulent motion can only wrinkle or distort the thin laminar flame zone. 1821…”
Section: Equivalent Operation Of the Engine Fuelled By Syngas And A S...mentioning
confidence: 99%
“…The work from Yontar predicted the characteristics of a hydrogen/butane dual sequential ignition engine adapting the G-equation as a combustion model [31]. Koch et al analyzed the effects of hydrogen enrichment on the methane internal combustion engine using Reynolds-averaged Navier-Stokes equation (RANS) and large eddy simulation (LES) with Gequation based turbulent flame speed modeling [32,33]. Tuncer et al showed that thermo-acoustic instability-induced flame flashback of hydrogen-enriched methane flames, which contain hydrogen fractions up to 50 %, could be captured using the Gequation, and its results showed good agreement with experiments [34].…”
Section: Introductionmentioning
confidence: 99%